HUBUNGAN KOMUNIKASI INTERPERSONAL DOKTER GIGI MUDA DENGAN MUTU PELAYANAN DITINJAU DARI KEPUASAN PASIEN DI KLINIK FAKULTAS KEDOKTERAN GIGI UNIVERSITAS ANDALAS - Rahmi Agvanesia; Zulkarnain Agus; Eni Rahmi (Andalas Dental Journal, 2014)
Background: Interpersonal Communication is a communication skill and it is one of the competencies that must be had by dentists, therefore, FKG UNAND has been trying to implement this soft skill by implementing it into curriculum. Patient satisfaction on interpersonal communication is thought to be one of the factors that determines the quality of a health service. The aim of the study is to determine whether there is a relationship between interpersonal communication of co-assistant students with service quality based on patient satisfaction at FKG UNAND clinic. Method: The study was an observational cross-sectional analytic approach. The sampling was simple random and the number of subjects were 90 respondents. The instruments used in this study were questionnaires consisting of 17 questions; they were 12 questions regarding interpersonal communication and 9 questions regarding patient satisfaction on service quality. Results: The result of chi-square test for interpersonal communication of co-assistant students-patient is p = 0.041 [p < 0.05]. This shows that there is a significant relationship between interpersonal communication of co-assistant students with service quality based on of patient satisfaction at FKG UNAND Clinic. Conclusion: There is relationship between interpersonal communication of co-assistant students and service quality based on of patient satisfaction at FKG UNAND Clinic.